2013
DOI: 10.1074/jbc.m112.416180
|View full text |Cite
|
Sign up to set email alerts
|

Neuronatin-mediated Aberrant Calcium Signaling and Endoplasmic Reticulum Stress Underlie Neuropathology in Lafora Disease

Abstract: Background: Neuronatin was identified as a novel substrate of Lafora disease ubiquitin ligase malin; however, its role in disease biology is unknown. Results: Neuronatin causes increased intracellular Ca 2ϩ and ER stress and accumulated as insoluble aggregates in LD brain and skin biopsy samples. Conclusion: Neuronatin-induced aberrant Ca ϩ2 signaling might trigger LD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
3
32
0
2
Order By: Relevance
“…Accordingly, the ectopic expression of Nnat in cultured neuronal cells results in increased intracellular Ca(2+), endoplasmic reticulum stress, proteasomal dysfunction and cell death. 35 In our experiments, Nnat levels appear significantly higher both in Foxg1+/ − whole brain and in silenced hippocampal neurons, strongly suggesting that this gene is directly or indirectly regulated by Foxg1.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Accordingly, the ectopic expression of Nnat in cultured neuronal cells results in increased intracellular Ca(2+), endoplasmic reticulum stress, proteasomal dysfunction and cell death. 35 In our experiments, Nnat levels appear significantly higher both in Foxg1+/ − whole brain and in silenced hippocampal neurons, strongly suggesting that this gene is directly or indirectly regulated by Foxg1.…”
Section: Discussionmentioning
confidence: 61%
“…In adult brain, Nnat is predominantly expressed in parvalbumin-positive GABAergic interneurons. Its levels are increased and accumulated as insoluble aggregates in the cortical area of patients with Lafora disease, a progressive and fatal neurodegenerative disease due to variants in Laforin and Malin genes; 35 in this condition, Nnat accumulation is accompanied by a dramatic loss of parvalbumin-positive GABAergic interneurons. Accordingly, the ectopic expression of Nnat in cultured neuronal cells results in increased intracellular Ca(2+), endoplasmic reticulum stress, proteasomal dysfunction and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…NNAT, an imprinted gene expressed from paternal allele, is down-regulated when PC12 cells undergo neuronal differentiation (Joseph et al, 1996;Zheng et al, 2002). Since high level of NNAT aggregates are found in Lafora disease (Sharma et al, 2011;Sharma et al, 2013) and phenylketonuria (Surendran et al, 2005), our data suggested that elevated NNAT expression may hinder the neuronal development in FXS patients.…”
Section: Discussionmentioning
confidence: 83%
“…Knowing that NNAT has a strong tendency to misfold and form cellular inclusions driving apoptotic cell death (Joseph, 2014), it is not surprising that the rodent ADRP models, experiencing severe cellular stress and apoptotic photoreceptor cell death (Kunte et al, 2012; Shinde et al, 2012) demonstrate partial accumulation of NNAT in the ONL of the retina. Possibly, the observed partial retention of NNAT is due to its ability to regulate Ca 2+ signaling and antagonize the SERCA2b pump (Sharma et al, 2013). Thus, in our previous study, we have found that both the aberrant Ca 2+ signaling and compromised SERCA2b activity were detected in S334ter and P23H RHO transgenic retinas (Shinde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mzhavia et al have also described the pathophysiological role of NNAT in diabetic vascular disease and have demonstrated NNAT-induced upregulation of NF-kB, increase in inflammatory gene expression, and the promotion of p38 and Jun-N signaling molecules in endothelial cells (Mzhavia et al, 2008). In patients with Lafora disease, NNAT has been reported to contribute to neuro pathogenesis by mediating aberrant Ca 2+ signaling, the activation of endoplasmic reticulum (ER) stress, and the formation of aggregates called Lafora bodies (Sharma et al, 2013). …”
Section: Introductionmentioning
confidence: 99%